Factors That Influence Companies in Tax Avoidance - Imelda Kristiani Panggabean; Kasir Kasir (Journal of Accounting Inaba, 2023)
The purpose of this study is to demonstrate how the bonus system, business size, and foreign ownership affect the effective tax rate for manufacturing companies listed on the Indonesian Stock Exchange between 2014 and 2021. This study employed a quantitative methodology that included a descriptive and verification approach. Secondary data are the ones that are used. Research from libraries and documentation from the Indonesian Stock Exchange's official website are used in the data collection process. Out of 40 firms, data was gathered for 7 Manufacturing firms using the Non-Probability Sampling approach. Partial testing research results indicate that while company size influences tax avoidance, the bonus structure and foreign ownership have little effect on tax avoidance. A coefficient of determination (R square) of 24.4% indicates that, for experiments conducted concurrently, the bonus method, firm size, and foreign ownership all have an impact on tax avoidance